Development of A Maize-Oriented Social Skill Based E-Module for Class V Elementary Schools - izza, roisyatul (Universitas Nahdatul Ulama Surabaya, 2024)
E-Modul is a form of media presentation of self-study teaching materials that are arranged systematically and presented electronically. The purpose of this development research is to produce e-modules based on social skills Corn-Oriented that are valid, practical and effective. This development research uses a 4D model consisting of 4 stages, namely (1) define (defining); (2) design (design); (3) develop (development); (4) disseminate . The subject of this research is the fifth grade students of SDN Gili Barat. The results of the validation of the learning design are 82.5%. The avarage results of the validation from linguists, materials experts and teaching materials design experts were 94.79%. The average result of the questionnaire responses of teachers and students is 98.69%. The results of the teacher activity observation sheet are 100%, the student activity observation sheet is 97.4% and the learning outcomes on the classical completeness criteria are 100%. The conclusion of this development research states that the corn-oriented social skills-based e-module is valid, interesting and effective so that it can be used in learning.